Social network, fair payment, subjective well-being, and general health: a moderation mediation analysis - Güler, Abdurrahim; Yıldırım, Murat; Gómez-Salgado, Juan (Frontiers in Public Health, 2024)
Objective This research aimed to investigate whether subjective general health mediated the relationship between social networks and subjective well-being and whether the perception of fair payment moderated the mediating effect of subjective general health on subjective well-being. Methods Data were drawn from round 9 of the European Social Survey (ESS), involving 3,843 respondents from 19 countries, with ages ranging from 65 to 90 years (Meanage = 73.88 ± 6.61 years). The participants completed self-reported measures assessing subjective well-being, social networks, subjective general health, and perception of fair payment. Results Subjective general health played a mediating role in the relationship between social networks and subjective well-being. The perception of fair payment emerged as a moderator in the mediating effect of subjective general health on the association between social networks and subjective well-being. Conclusion This study suggests that the impact of social networks on both subjective general health and subjective well-being is contingent upon individuals’ perceptions of fair payment. These results highlight the significance of social networks in fostering social connections and promoting overall subjective well-being.